Image-guided Localization Techniques for Nonpalpable Breast Lesions: An Opportunity for Multidisciplinary Patient-centered Care. Issue 5 (30th August 2021) - Davis, Katie M; Raybon, Courtney P; Monga, Natasha; Waheed, Uzma; Michaels, Aya; Henry, Cameron; Spalluto, Lucy B
Abstract: Selection of a localization method for nonpalpable breast lesions offers an opportunity for institutions to seek multidisciplinary input to promote value-based, patient-centered care. The diverse range of nonpalpable breast and axillary pathologies identified through increased utilization of screening mammography often necessitates image-guided preoperative localization for accurate lesion identification and excision. Preoperative localization techniques for breast and axillary lesions have evolved to include both wire and nonwire methods, the latter of which include radioactive seeds, radar reflectors, magnetic seeds, and radiofrequency identification tag localizers. There are no statistically significant differences in surgical outcomes when comparing wire and nonwire localization devices. Factors to consider during selection and adoption of image-guided localization systems include physician preference and ease of use, workflow efficiency, and patient satisfaction.